Influence of Fe doping and magnetic field on martensitic transition in Ni–Mn–Sn melt-spun ribbons. (1st April 2016) - Aguilar-Ortiz, C.O.; Soto-Parra, D.; Álvarez-Alonso, P.; Lázpita, P.; Salazar, D.; Castillo-Villa, P.O.; Flores-Zúñiga, H.; Chernenko, V.A.
Abstract: Mn-rich Ni–Mn–Sn metamagnetic shape memory alloys exhibiting magnetostructural transformation are of a great potential as the base materials for solid-state refrigeration. With the aim of fine tuning of the transformation characteristics and improving functional properties, in the present work we have fabricated polycrystalline Ni50-x Fex Mn40 Sn10 (x = 0, 2, 4, 6, 8 at.%) melt-spun ribbons, starting from the base alloy with x = 0, which is weakly magnetic in both austenitic and martensitic phases. By exploring martensitic transformation (MT) and magnetic behaviors as a function of Fe doping and magnetic field, we have found that Fe and/or magnetic field reduce the MT temperature and Curie temperature of austenite phase, becoming closer to each other as the Fe-content increases, accompanied by an increase of the magnetic moment of austenite, magnetization jump at MT, transformation volume, and magnetic contribution, ΔSM, to the total entropy change at MT. The ribbons present moderate values of ΔSM equal to 11 J kg −1 K −1 at 5 T for x = 8, moderate thermal hysteresis (10–14 K) nearly independent of Fe doping or magnetic field, and adjustable structural and magnetic transition temperatures close to room temperature. Graphical abstract: Effect of Fe-doping on martensitic and magnetic phase transitions and magnetocaloric effect iMn Ni50-x Fex Mn40 Sn10 ribbons (x = 0, 2, 4, 6, 8).